Membangun Akhlak Islami Sebagai Pondasi Tumbuh Kembang Anak yang Berkarakter di Era Modern (Laporan Pengabdian kepada Masyarakat di Desa Imbanagara Raya, Kecamatan Ciamis, Kabupaten Ciamis) - Firdaus, Agus; Fauzan, Fahmi Azka; Hoirunnisa, Fuja; Triani, Irda; Fitriah, Lela Lailatul; Aulia, Rahma; Handayani, Rani; Solehudin, Rifqi; Utami, Sasti Dwi; Sumarni, Sri; Hayatunnufus, Alifa Baiduri (Khidmat, 2023)
Education is an institutional mechanism that can accelerate the development of national character. The factors that influence the decline of the Indonesian nation are mental decay and the collapse of morals, both in the older generation and also in the younger generation, both in the ranks of government and among the wider community. These things resulted in the Indonesian nation experiencing setbacks in various positions in the world. To overcome these problems, the Indonesian nation must foster and build life by instilling positive values ​​so that the Indonesian nation has a positive character and is able to compete with other countries in the era of globalization. The character of education that has great opportunities to carry out the process of fostering and developing humanity is education that is based on noble morals, namely Islamic education that combines 'aqidah, shari'ah, and morals in a learning structure that has an Islamic moral character. In overcoming the problems of national life, it is necessary to realize character education in educational development, both formal, non-formal and informal education, starting in the family environment, at the early childhood, childhood and adult levels. Inner improvement is the basis for external improvement, and external improvement will not be permanent unless it is carried out centrally and has an influence on inner improvement. One of the virtues of Al-Islam for humanity is the existence of a complete and consistent method in developing mental development, giving birth to generations, developing people and culture, and enforcing the principles of glory and civilization. Children's educators must continue to look for more effective methods, look for educational principles that are influential in preparing children mentally and morally, scientifically, spiritually and socially, so that children can achieve perfect maturity.